Medications and Follow-Up Adherence of Children with Nephrotic Syndrome (Iraqi Journal of Medical Sciences, 2024)
Background: Nephrotic syndrome is one of the most common chronic kidney diseases in children. Its management requires outpatient follow-up and family engagement.Objective: To evaluate the adherence of patients with nephrotic syndrome to the scheduled follow-up visits to the outpatient clinics, and to assess the possible risk factors for non-adherence. Methods: A prospective observational study was carried out on 96 patients with nephrotic syndrome over a period of 1 year. Both regularly scheduled and urgent visits to the outpatient nephrology clinic were recorded. If a patient missed more than 20% of their scheduled clinic appointments throughout the follow-up period, they were considered to be non-adherent.Results: Frequent relapse was the most common presentation encountered in 43.75% of the patients, and the median disease duration was 3.12 years (range 0.25-13.0 years). The study showed that 71 patients (73.96%) had good adherence, while 25 patients (26.04%) were non-adherent. More than half of non-adherent patients (56%) were rural residents. The median disease duration in adherent and non-adherent patients was 3.0 and 4.0 years, respectively, with a significant difference. Furthermore, frequent relapse was more common among non-adherent than adherent patients (64% vs. 36.62%), while steroid-resistant nephrotic syndrome was more common among adherent (21.13%) than non-adherent patients (4%) with a significant difference.Conclusion: Non-adherence was significantly correlated with residency in rural areas and longer disease duration. Frequently-relapsing nephrotic syndrome was more common among non-adherent than adherent patients, while steroid-resistant type was more common among adherents, with a significant difference.Keywords: Nephrotic syndrome, non-adherence, risk factorsCitation: Hussein SA, Ali SH. Medications and follow-up adherence of children with nephrotic syndrome. Iraqi JMS. 2024; 22(1): 45-53. doi: 10.22578/IJMS.22.1.6
Keywords: Nephrotic syndrome; nonadherence; risk factors